Modelagem e desenvolvimento de um banco de dados geográficos : aplicação à elaboração de mapas de sensibilidade ambiental ao derramamento de óleo na área costeira entre Galinhos e São Bento do Norte-RN - Castro, Angélica Félix de (2002)
The area between Galinhos and São Bento do Norte beaches, located in the northern coast of the Rio Grande do Norte State is submitted to intense and constant processes of littoral and aeolian transport, causing erosion, alterations in the sediments balance and modifications in the shoreline. Beyond these natural factors, the human interference is huge in the surroundings due to the Guamaré Petroliferous Pole nearby, the greater terrestrial oil producing in Brazil. Before all these characteristics had been organized MAMBMARE and MARPETRO projects with the main objective to execute the geo-environmental monitoring of coastal areas on the northern portion of RN. There is a bulky amount of database from the study area such as geologic and geophysical multitemporal data, hydrodynamic measurements, remote sensing multitemporal images, thematic maps, among others; it is of extreme importance to elaborate a Geographic Database (GD), one of the main components of a Geographic Information System (GIS), to store this amount of information, allowing the access to researchers and users. The first part of this work consisted to elaborate a GD to store the data of the area between Galinhos and São Bento do Norte cities. The main goal was to use the potentiality of the GIS as a tool to support decisions in the environmental monitoring of this region, a valuable target for oil exploration, salt companies and shrimp farms. The collected data was stored as a virtual library to assist men decisions from the results presented as digital thematic maps, tables and reports, useful as source of data in the preventive planning and as guidelines to the future research themes both on regional and local context. The second stage of this work consisted on elaborate the Oil-Spill Environmental Sensitivity Maps. These maps based on the Environmental Sensitivity Index Maps to Oil Spill developed by the Ministry of Environment are cartographic products that supply full information to the decision making, contingency planning and assessment in case of an oil spilling incident in any area. They represent the sensitivity of the areas related to oil spilling, through basic data such as geology, geomorphology, oceanographic, social-economic and biology. Some parameters, as hydrodynamic data, sampling data, coastal type, declivity of the beach face, types of resources in risk (biologic, economic, human or cultural) and the land use of the area are some of the essential information used on the environmental sensitivity maps elaboration. Thus using the available data were possible to develop sensitivity maps of the study area on different dates (June/2000 and December/2000) and to perceive that there was a difference on the sensitivity index generated. The area on December presented more sensible to the oil than the June one because hydrodynamic data (wave and tide energy) allowed a faster natural cleaning on June. The use of the GIS on sensitivity maps showed to be a powerful tool, since it was possible to manipulate geographic data with correctness and to elaborate more accurate maps with a higher level of detail to the study area. This presented an medium index (3 to 4) to the long shore and a high index (10) to the mangrove areas highly vulnerable to oil spill